THE USE OF GRAPHIC ORGANIZERS TO IMPROVE STUDENTS’ WRITING SKILL OF JUNIOR HIGH SCHOOL - Berlidio Rizky Agasi (English Research Journal : Journal of Education, Language, Literature, Arts and Culture, 2018)
The objectives of this research are (1) to find out whether Graphic Organizers can improve writing skill of Eight Grade students of SMP N 4 Sukoharjo in 2017/ 2018Academic Year (2) to find out how is the class condition when Graphic Organizers is implemented in writing class at Eight Grade of SMP N 4 Sukoharjo in 2017/2018Academic Year. This researcher held from January 2017 to January 2018. In this research, the researcher conducted two cycles. Each cycle consisted of two meetings and one posttest. Each cycle had four steps: planning, action, observation, and reflection.  In  collecting  the  data,  the  researcher  used  observation,  interview, document, and test. In analyzing the data, the researcher used quantitative and qualitative data analysis. The researcher conducted pre-test, post-test 1 and post-test 2 to get raw data. After the researcher had the data, the researcher calculated the mean score from the pretest, post test1 and posttest 2. The researcher also calculated t-value using t-test. The result of this research shows that there was improvement in students’ writing  skill.  Based  on  the  mean  score  of  the  students  in  pre-test  was  19,34, meanwhile in the post-test I of cycle I, it increased to 60,5. In the post-test II of cycle II the value had increased to average value 72,9. Besides, the class condition was better where the students’ enthusiasm was increased to learn English. The students were able to transform their idea into written form using graphic organizers. Based on the  result  above,  it  can  be  concluded  that  (1)  Graphic  Organizers  strategy  can improve  students’  writing  skill  in  class  VIII  G  of  SMP  Negeri  4  Sukoharjo  in2017/2018   Academic   Year   and   (2)   class   condition   was   better   after   the implementation of Graphic Organizers strategy. Graphic Organizers strategy can be new way in teaching learning to improve students’ writing skill.